The Development of Sustainability Reports In Indonesia: Management Approaches and Performance Indicators (Case Study in the Energy Sector 2020-2024) - Chairina Chairina; Novita Weningtyas Respati; Rasidah Rasidah; Muhammad Nordiansyah; Enny Hardi (Master of Management FEB ULM, 2026)
The issue of sustainability reports is a growing concern impacting numerous domestic and international companies. This phenomenon can be attributed to the emergence of sustainability report practices, which enhance corporate image and ensure corporate sustainability. This study utilizes a comprehensive dataset to assess the sustainability reports of Indonesian companies. The analysis employs two distinct types of information: a management approach to the extent of corporate governance disclosure and performance indicators (economic, environmental, and social performance) in sustainability disclosure reporting. A longitudinal approach was employed to evaluate developments up to 2020 – 2024, specifically for companies operating dengan 222 sampel in the energy sector , because the energy sector is an industry with a fairly significant operational impact on the environment. The content analysis framework aligns with the Global Reporting Initiative (GRI) Standards. The findings indicate a positive development in the disclosure of information types, with companies reporting an average governance performance of 77.77% in corporate management. However, the disclosure of economic performance indicators (39.57%), environmental performance (40.47%), and social performance (47.05%) was found to be lower. Aggregate EESG (economic, environmental, social, and governance) disclosure was 48.68%. The quantity of information utilized exhibited considerable variation across diverse sustainability domains. This study also conducted additional testing by performing statistical tests to examine the impact of the disclosure of these two types of information (management approach-performance indicators) on financial performance. The findings indicate that economic and social indicators exert a substantial influence on financial performancems.